What Drives Embryo Development? Chromosomal Normality or Mitochondria? - A. Bayram; I. Elkhatib; A. Arnanz; A. Linan; F. Ruiz; B. Lawrenz; H. M. Fatemi (Case Reports in Genetics)
Objective. To report the arrest of euploid embryos with high mtDNA content. Design. A report of 2 cases. Setting. Private fertility clinic. Patients. 2 patients, 45 and 40 years old undergoing IVF treatment. Interventions. Mature oocytes were collected and vitrified from two ovarian stimulations. Postthaw, survived mature oocytes underwent fertilization by intracytoplasmic sperm injection (ICSI). Preimplantation genetic screening (PGS) and mitochondrial DNA (mtDNA) copy number were done using next generation sequencing (NGS). The only normal embryo among the all-biopsied embryos had the highest “Mitoscore” value and was the only arrested embryo in both cases. Therefore, the embryo transfer was cancelled. Main Outcome Measures. Postthaw survival and fertilization rate, embryo euploidy, mtDNA copy number, and embryo development. Results. In both patients, after PGS only 1 embryo was euploid. Both embryos had the highest mtDNA copy number from all tested embryos and both embryos were arrested on further development. Conclusions. These cases clearly demonstrate the lack of correlation between mtDNA value (Mitoscore) and chromosomal status of embryo.